Neurologic Complications of Extracorporeal Cardiopulmonary Resuscitation in Neonates and Infants. (September 2022) - Schmaedick, Maggie J.; Midura, Devin; Gerall, Claire D.; Garey, Donna; Middlesworth, William; Bain, Jennifer M.
Objective: Extracorporeal membrane oxygenation (ECMO) is a lifesaving measure for patients in cardiac or respiratory failure. Extracorporeal cardiopulmonary resuscitation (ECPR) is emergent ECMO cannulation during cardiac arrest. All ECMO patients are at high risk for neurologic complications, but the degree of risk of ECPR relative to ECMO without CPR in progress (non-ECPR ECMO) is not well documented in infants. The goal of the present study is to compare neurologic complication rates between infants who underwent ECPR and those who underwent non-ECPR ECMO.Methods: We performed a retrospective chart review on all patients admitted between 2009 and 2020 to the neonatal intensive care unit (NICU) in our quaternary children's hospital. We separated patients by ECPR vs. non-ECPR ECMO cannulation. We compared rates of death and used neuroimaging and video electroencephalogram (vEEG) to determine incidence of stroke, intracranial hemorrhage, and seizure. Chi-square and Fisher's exact tests were used to compare these categorical variables among groups.Results: A total of 181 infants were cannulated onto ECMO. Of these, 40 received ECPR, 56 received non-ECPR ECMO for a cardiac indication, and 85 received non-ECPR ECMO for a respiratory indication. After excluding patients currently admitted (n=1, ECPR), 180 patients were subjected to analysis. ECPR patients were less likely to survive to hospital discharge than patients who underwent non-ECPR ECMO for respiratory indications, and less likely to survive without any neurologic complication compared with infants who underwent non-ECPR ECMO for cardiac or respiratory indications.Interpretation: Significantly fewer ECPR patients survived without experiencing a neurologic complication, compared with non-ECPR ECMO patients.